Examining the Transformative Effect of the RADEC Learning Model on Student’s Fictional Writing Ability - Three Rahmadona; Syafri Ahmad; Elfia Sukma; Yanti Fitria (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study originated from the observation of teachers employing traditional teaching methods, leading to a notable deficiency in students' proficiency in crafting fiction texts. The aim of this research is to investigate the impact of the RADEC (Read, Answer, Discuss, Explain, Create) learning model on the development of fiction writing skills among fifth-grade elementary students. Employing a quasi-quantitative experimental approach, this study utilizes a non-equivalent control group design, incorporating experimental and control classes. Data collection methods include observation, pretest and posttest assessments, and documentation. Data analysis involves normality testing, homogeneity of variance testing, and independent sample testing using SPSS IBM26. The findings reveal a statistically significant disparity in the average fiction writing ability between groups utilizing the RADEC model and conventional methods, with a significance value of 0.047 0.05. The noteworthy average improvement of 17.5 in students' fiction writing skills subsequent to the implementation of the RADEC learning model underscores its effectiveness, advocating for its adoption by educators, particularly for enhancing the writing proficiency of fifth-grade students.